Creative Writing and Lampung Language Revitalization for Generation Z in Literary Camp - Fitri Angraini (EDUJAVARE: International Journal of Educational Research, 2026)
This study aims to describe the application of the Literary Camp method in creative writing in the field of Lampung language literature for Generation Z. The study used a qualitative method with a descriptive approach. The research subjects were 20 literary camp participants consisting of junior high school students, high school students, and university students throughout Lampung. The study was conducted at Villa Dangau Kedaung, Lampung, on April 6-9, 2026. Data collection techniques included participant observation, documentation of literary works, and in-depth interviews. Data were analyzed using the Miles, Huberman, and Saldana model through the stages of data reduction, data presentation, and drawing conclusions. Data validity was guaranteed through triangulation of sources and methods. The results of the study showed that: (1) the literary camp method significantly improved the quality of participants' creative writing, both in terms of diction, local wisdom themes, and courage to express themselves; (2) the process of translating literary works from Indonesian to Lampung (Pepadun and Saibatin dialects) was successfully carried out by participants with academic guidance; and (3) an anthology of literary works entitled Seaninongan Batas Atas yang Dijaga Angin, which contains 38 works (11 short stories and 27 poems), was successfully published as the final product of the program. It can be concluded that the literary camp method is effective as a local culture-based learning model to increase literary literacy while encouraging the preservation of the Lampung language among generation Z.